The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1029/2008ja013149
|View full text |Cite
|
Sign up to set email alerts
|

Observations of small‐ to large‐scale ionospheric irregularities associated with plasma bubbles with a transequatorial HF propagation experiment and spaced GPS receivers

Abstract: [1] The results from simultaneous observations of the nighttime transequatorial propagation (TEP) of HF radio waves between Australia and Japan and the GPS scintillation measurements in south China and Vietnam are presented in this paper. The results showed that there was good correspondence between the nighttime eastward traveling off-great circle propagation (OGCP) of broadcasting waves of Radio Australia from Shepparton, Australia, measured at Oarai, Japan, and the scintillations in GPS radio waves at Haina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…Maruyama and Kawamura (2006) observed HF-TEP from Australia to Japan and showed that directions of arrival (DOAs; azimuth and elevation angles) measurements of transequatorial propagating HF radio waves enables us to monitor the existence of plasma Radio Science 10.1029/2017RS006518 bubbles as well as to estimate their drift velocity. Saito et al (2008) showed that the drift velocities estimated by the HF-TEP DOA measurements were consistent with plasma bubble drift velocities estimated by GPS measurements for their data set obtained in 1 month. However, Tsunoda et al (2016a) pointed out that abnormally fast velocities were sometimes obtained from the HF-TEP DOA measurements.…”
Section: Introductionsupporting
confidence: 80%
“…Maruyama and Kawamura (2006) observed HF-TEP from Australia to Japan and showed that directions of arrival (DOAs; azimuth and elevation angles) measurements of transequatorial propagating HF radio waves enables us to monitor the existence of plasma Radio Science 10.1029/2017RS006518 bubbles as well as to estimate their drift velocity. Saito et al (2008) showed that the drift velocities estimated by the HF-TEP DOA measurements were consistent with plasma bubble drift velocities estimated by GPS measurements for their data set obtained in 1 month. However, Tsunoda et al (2016a) pointed out that abnormally fast velocities were sometimes obtained from the HF-TEP DOA measurements.…”
Section: Introductionsupporting
confidence: 80%
“…For example, the lengths of great-circle TEP paths (1) from Tsumeb (19.3°S, 17.7°E) to Lindau (51.4°N, 10.1°E) (Röttger 1973), and (2) from Shepparton (36.2°S, 135.3°E) to Oarai (36.3°N, 140.6°E) (Maruyama and Kawamura 2006;Saito et al 2008), were both about 8,000 km. With this viewing geometry, signals that arrive at azimuths ±60°a way from the great-circle path have been detected.…”
Section: Transequatorial Propagation Resultsmentioning
confidence: 99%
“…The correlation is better near the magnetic equator than near the crests. The previous studies showed that the scintillation occurrence in the low-latitude region is almost associated with plasma bubble (Rama Rao et al, 2006;Saito et al, 2008;Abadi et al, 2014;Bhattacharyya et al, 2014). The scintillations are due to ionospheric irregularities generated at the equatorial region through RT plasma instability, which is considered as the primary mechanism responsible for the generation of plasma bubble.…”
Section: Scintillation Climatology In the Vietnam Regionmentioning
confidence: 99%